Synthesis of Bio-Inspired 1,3-Diarylpropene Derivatives via Heck Cross-Coupling and Cytotoxic Evaluation on Breast Cancer Cells - Aik Sian Tan; Jaymeer Singh; Nurul Syafiqah Rezali; Musthahimah Muhamad; Nik Nur Syazni Nik Mohamed Kamal; Yvan Six; Mohamad Nurul Azmi (Molecules, 2022)
The Heck cross-coupling reaction is a well-established chemical tool for the synthesis of unsaturated compounds by formation of a new C-C bond. In this study, 1,3-diarylpropene derivatives, designed as structural analogues of stilbenoids and dihydrostilbenoids, were synthesised by the palladium-catalysed reactions of 2-amidoiodobenzene derivatives with either estragole or eugenol. The products were obtained with high (E) stereoselectivity but as two regioisomers. The ratios of isomers were found to be dependent on the nature of the allylbenzene partner and were rationalised by electronic effects exercising a determining influence in the β-hydride elimination step. In addition, the cytotoxic effects of all the Heck reaction products were evaluated against MCF-7 and MDA-MB-231 human breast cancer cells, with unpromising results. Among all, compound 7d exhibited weak cytotoxic activity towards MCF-7 cell lines with IC50 values of 47.92 µM in comparison with tamoxifen and was considered to have general toxicity (SI value < 2).